2012
DOI: 10.1186/1471-2458-12-83
|View full text |Cite
|
Sign up to set email alerts
|

A local outbreak of dengue caused by an imported case in Dongguan China

Abstract: BackgroundDengue, a mosquito-borne febrile viral disease, is found in tropical and sub-tropical regions around the world. Since the first occurrence of dengue was confirmed in Guangdong, China in 1978, dengue outbreaks have been reported sequentially in different provinces in South China transmitted by.peridomestic Ae. albopictus mosquitoes, diplaying Ae. aegypti, a fully domestic vector that transmits dengue worldwide. Rapid and uncontrolled urbanization is a characteristic change in developing countries, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 12 publications
0
60
1
Order By: Relevance
“…Community-based measures focused mainly on: involvement and training of community volunteers [33, 35, 36, 38, 49] ( n =  5, 16%); awareness campaigns [20, 30, 31, 40, 41] ( n =  5, 16%); and public education [31, 33, 41, 49] ( n =  4, 13%). They also included community-based surveillance or case-finding [30, 35, 36] ( n =  3, 10%) and social mobilization [22, 36] ( n =  2, 6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based measures focused mainly on: involvement and training of community volunteers [33, 35, 36, 38, 49] ( n =  5, 16%); awareness campaigns [20, 30, 31, 40, 41] ( n =  5, 16%); and public education [31, 33, 41, 49] ( n =  4, 13%). They also included community-based surveillance or case-finding [30, 35, 36] ( n =  3, 10%) and social mobilization [22, 36] ( n =  2, 6%).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons included: high population density [20, 23, 24, 32, 39, 47]; population mobility [30, 32, 35]; and rapid, unplanned urbanization [31, 32]. One article mentioned the lack of community involvement and absence of strong social networks as challenges related to infectious disease control in urban settings.…”
Section: Resultsmentioning
confidence: 99%
“…A. albopictus was found in the Americas in 1985 and is currently present in 8 American countries (Pinheiro and Nelson, 1997). In China, Peng et al (2012) reported the re-emergence of dengue in a city in southern China 2 decades after a traveler from Southeast Asia introduced A. albopictus. Thus, examining the population genetic structure is important for understanding the evolution of this species (Hewitt, 1983), which may lead to novel methods of controlling disease transmission (Ayres et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Alanine aminotransferase (ALT) levels reached 114 U L −1 , which is approximately three times higher than the upper limit of normal; aspartate aminotransferase (AST) reached 152 U L −1 , which was more than four times higher than the highest normal level; and serum albumin was slightly decreased at 32 g L −1 . The DG14 strain, which was the strain most closely related to GZ02 from Guangdong, was not associated with liver damage (Peng et al 2012). Replication kinetics of DG14, DENV-1 Hawaii (the standard strain), and GZ02 strains were compared in human normal liver cells L02.…”
Section: Resultsmentioning
confidence: 99%
“…According to epidemiological data, strains from countries that had introduced DENV into Guangdong in the past few years were chosen for genetic analysis (Sang et al 2015; Peng et al 2012). Based on the percent nucleotide and amino acid identities to GZ02, one DENV-1 strain from each of these countries was chosen for phylogenetic analysis of the complete genome (Fig.…”
Section: Discussionmentioning
confidence: 99%